A STUDY ON THE EFFECT OF PLASTIC IN THE AGRICULTURE FIELD IN PASCHIM MEDINIPUR DISTRICT, WEST BENGAL - 1. Krishna Roy , 2. Dr. G.L. Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The study is based on providing a detailed understanding of the uses of plastic bags and their impact on the environment and agriculture of Paschim Medinipur. The study has provided a detailed understanding and overview of the topic that includes an understanding of the emerging issues associated with the use of plastic bags. It also highlights the significance of conducting this research to the specific region of Paschim Medinipur. The study is also helpful in providing the overall research objectives and aims along with the research questions. The research hypotheses are also effectively represented in the introduction chapter aligning with the problem statement and research rationale. The study further describes the structure that has been followed throughout the research. The use of plastic is increasing day by day and it is effective on human health, animals and agriculture. This evaluation urges to gain insight into different types of plastic used in agricultural fields and their impact. Other than that, this research is effective in bringing forth the short and long term effect of using plastic in agricultural land. Therefore, the main purpose of this chapter of the thesis is to demonstrate the effect of using plastic in agricultural land. Other than that, the research is also significant in bridging forth the health risk of using plastic. The study is based on providing a detailed understanding of the uses of plastic bags and their impact on the environment and agriculture of Paschim Medinipur. The study has provided a detailed understanding and overview of the topic that includes an understanding of the emerging issues associated with the use of plastic bags. It also highlights the significance of conducting this research to the specific region of Paschim Medinipur. The study is also helpful in providing the overall research objectives and aims along with the research questions.